STRATEGI KOPING MAHASISWA TINGKAT AKHIR DALAM MENYELESAIKAN SKRIPSI - Macawalang, Nadya Natallie Steni; Purnawinadi, I Gede (Fakultas Keperawatan, Universitas Klabat, 2025)
Final-year students often face academic, psychological, and environmental pressures in the process of writing their theses. This condition requires the use of effective coping strategies, but not all students are able to manage them adaptively, putting them at risk of stress and delays in completing their theses. This study aims to determine the differences in coping strategies among final year students who are writing their thesis at Klabat University. The method used was an analytical survey with a comparative model through a cross-sectional approach on the population of final year students at Klabat University, calculated using the Slovin formula with a total of 236. The sampling technique used is Purposive Sampling, and the data is analyzed using the Kruskal Wallis statistical test. The results show that the majority of 234 (99.2%) respondents have excellent coping strategies, while only 2 respondents (0.8%) have good coping strategies. There is a significant difference in coping strategies based on faculty among final year students who are writing their thesis at Klabat University, with a p-value of 0.038 < 0.05. Recommendations for students writing their thesis are to apply good adaptive coping strategies to prevent academic stress, for educational institutions to create activities that build mental health, and for future researchers to conduct research on factors that influence coping strategies. Mahasiswa tingkat akhir sering menghadapi tekanan akademik, psikologis, dan lingkungan dalam proses penyusunan skripsi. Kondisi ini menuntut penggunaan strategi koping yang efektif, namun tidak semua mahasiswa mampu mengelolanya secara adaptif sehingga berisiko menimbulkan stres dan keterlambatan penyelesaian skripsi. Penelitian ini bertujuan untuk mengetahui perbedaan koping pada tingkat akhir yang sedang menulis skripsi di Universitas Klabat. Metode yang digunakan yaitu survei analitik dengan model komparatif melalui pendakatan cross-sectional pada populasi mahasiswa tingkat akhir di Universitas Klabat yang dihitung menggunakan rumus slovin dengan jumlah 236. Teknik pengambilan sampel menggunakan Purposive Sampling serta data dianalisis menggunakan uji statistik Krulkal Wallis. Hasil penelitian menunjukkan mayoritas sebanyak 234 (99,2%) responden memiliki koping yang sangat baik sedangkan hanya 2 responden (0,8%) memiliki koping baik. Terdapat perbedaan koping yang signifikan berdasarkan setiap fakultas pada mahasisiwa tingkat akhir yang sedang menyusun skripsi di Universitas Klabat didapati p-value = 0.038 < 0,05. Rekomendasi untuk mahasiswa yang sedang menyusun skripsi untuk dapat mencegah stress akademik dengan menerapkan koping yang baik secara adaptif, untuk institusi pendidikan agar bisa membuat kegiatan yang membangun kesehatan mental, untuk peneliti selanjutnya dapat melakukan penelitian tentang faktor-faktor yang mempengaruhi strategi koping.